Evaluation of Cytotoxic and Antioxidant Activity and Total Phenolic Content of Some Soft Corals from the Persian Gulf: Cytotoxic, Antioxidant Activity and Total Phenolic Content of Persian Gulf Soft Corals - Yegdaneh, Afsaneh; Mohammadi Pour, Pardis; Mohammadi, Elmira; Mehdinezhad, Negin; Shabani, Leila (Iranian Journal of Pharmaceutical Sciences, 2020)
Marine soft corals contain a variety of secondary metabolites with diverse, biological activities, including cytotoxic and anti-oxidant. The aim of this study was to evaluate the total phenolic content, antioxidant and cytotoxic activities of some soft corals of Persian Gulf including: Junceella juncea, Cavernularia sp., white Menella sp., brown Menella sp., Virgularia sp., Sinularia compressa, Sinularia variablis and Sinularia polydactyla were collected from Persian Gulf and extracted by maceration with methanol-ethyl acetate (1:1) solvent. The extract was evaporated and the total phenolic content was evaluated by using the Folin-ciocalteu reagent. The antioxidant activity of corals was tested by using DPPH photometric assay and cytotoxic activity of them against MCF-7 and OVCAR-3 cancer cell lines were performed. The cell survivals of MCF-7 and OVCAR-3 cell lines were decreased by increasing the concentration of the extracts. The brown Menella sp. showed the highest cytotoxic activity against MCF-7 with IC50 values of 325.45±2.57 μg/ml and S. polydactyla showed the highest cytotoxic activity against OVCAR-3 cell line with IC50 values of 260.99±7.93 μg/ml. White Menella sp. showed the highest antioxidant activity with IC50 values 0.056 μg/ml. Finally Cavernularia sp. had the most polyphenol content with 186.33 mg/L. Key words: soft corals, antioxidant DPPH photometric assay, total phenolic content, Folin–Ciocalteu method, cytotoxic activity, Persian Gulf.